An analysis on benefits of ISO 14001 and enviromental performance in Foamline Industries Sdn. Bhd. [microfilm] - Fakulti Pengurusan dan Pembangunan Sumber Manusia (2007)
Project Paper (Sarjana Muda) - Universiti Teknologi Malaysia, 2007